SUSTAINABLE BUILDING MATERIAL COMPARISON BETWEEN THAILAND AND INDONESIA – TARBIATULWATAN MULNITI SCHOOL, PATTANI - Setiawan, Agus; Carina, Annisa'; Dueramaeng, Wael; Yuniar Caroline, Vanezia (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
This study compares sustainable building materials used in Thailand and Indonesia, focusing on the case of Tarbiatulwatan Mulniti School in Yala, Thailand, as part of an international community service (KKN Internasional) program. The research aims to identify the differences in material selection, sustainability performance, and cultural adaptation in both countries. The methods used include field observation, literature review, and comparative analysis based on material efficiency, environmental impact, cost, and social acceptance. The results show that Thailand adopts more sustainable materials, such as Autoclaved Aerated Concrete (AAC) blocks, light steel trusses, and energy-efficient coatings, supported by national policies like the Thai Green Building Standard (TGBS). In contrast, Indonesia still relies on traditional red bricks and reinforced concrete, which are cheaper and widely available but less environmentally friendly. The study concludes that Thailand’s approach demonstrates stronger integration of policy, technology, and cultural awareness toward sustainability, while Indonesia’s construction practices remain cost-oriented. The research recommends that Indonesia strengthen green building policies, improve public awareness, and promote cross-national collaboration to accelerate sustainable construction development.